Pengaruh Germinasi terhadap Sifat Fisikokimia dan Organoleptik Flakes Tepung Kedelai Putih (Glycine max L.) - Nirwesthi, Kartika K; Suhartatik, Nanik; Nuraini, Vivi (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Flakes were included in ready-to-eat food and can be consumed as a main meal or a snack. Flakes need to have good nutritional content and be high in protein for breakfast. Soybean flour can be utilized as a vegetable protein. This study employed germinated white soybeans and white glutinous rice flour. Germination is an active process of embryonic development in which the seed coat breaks, causing new individuals to grow. Refined soy flour was used to increase protein and antioxidant activity, as well as flavonoid content in the flakes. The study aimed to determine the best formulation and the effects of soybean germination time and variations in the concentration of germinated soybean flour with glutinous rice flour on the physicochemical and sensory characteristics of the flakes. The experimental design employed was a completely randomized design with two factors: germination time (0, 24, and 48 h) and the ratio of soybean flour to glutinous rice flour (30:70, 50:50, and 70:30). This research comprised nine formulas. The best results based on physicochemical factors of increased antioxidants, protein, and flavonoid content, as well as sensory characteristics, were achieved with 24 h germination of soybeans, 70 g of soybean flour, and 30 g of glutinous rice flour. The selected products exhibited the following attributes: moisture content 6.19%, total ash 4.02%, protein 28.32%, fats 6.83%, carbohydrates 54.64%, crude fiber 22.73%, antioxidant activity 16.11%, flavonoids 1.58 mg QE/g, rehydration 36.80%, hardness 11.84 N, color 3.1, aroma 3.05, texture 3.1, taste 3.12, and overall acceptance 3.3. Germinated soybeans have the potential to be used as a source of protein for snacks.